Freedom within a framework : hearing the voice of the customer on the factory floor - Cafaro, Paul G. (New York : Productivity Press, 2020)
Freedom Within a Framework: Hearing the Voice of the Customer on the Factory Floor (978-0-367-08577-3, K406714) Shelving Guide: Business and Management/Customer Satisfaction/Quality This book shows you how to harmonize three business functions to address customer needs by using a novel approach that combines Design for Six Sigma (DFSS) and Continuous Improvement tools. The DFSS tool used is the Quality Function Deployment (QFD) process, which is also known as the House of Quality (HOQ). Although these are techniques reserved for the design of new products, the book illustrates how the HOQ helps translate exactly what customers specifically find important about your products. In addition, if customers are experiencing issues with that product, it helps map those issues and prioritizes the Critical to Quality (CTQ) parameters. Because the HOQs tie the Voice of the Customer to CTQs, it continues to connect to the product design and ends with manufacturing process variables. This linkage makes this idea and approach unique. Stopping there may show that there is linkage between the customer and manufacturing process variables, but moving ahead, we must also connect the functions within the business that provides the product. The book helps define the key business function as three large business functions that must work as one cohesive and unified team. These functions are: commercial (sales and marketing), R&D (product properties and services), and operations (product quality). Connecting these functions involves many colleagues, and a very effective communication process among the three is vital for the success of the product and customer satisfaction. Understanding the voice of the customer is paramount--not doing so could lead to product performance issues and loss of market share. In addition, repeated customer dissatisfaction permeates internal workplace culture--employees begin to feel that they are producing products disconnected from end users' needs and wants.
OCLC-licensed vendor bibliographic record.
Keywords: Consumer satisfaction; Quality control; Production management; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Production & Operations Management